2012
DOI: 10.1210/jc.2011-3428
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Death-1+ T Cells and Regulatory T Cells Are Enriched in Tumor-Involved Lymph Nodes and Associated with Aggressive Features in Papillary Thyroid Cancer

Abstract: Increased Treg and PD-1(+) T cell frequencies in LN may be indicative of aggressive recurrent PTC. Future prospective studies are necessary to determine the prognostic and therapeutic value of these findings in PTC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
115
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(124 citation statements)
references
References 36 publications
8
115
0
1
Order By: Relevance
“…Lymph node metastatic tissues had lower levels of B7H1 than the primary tumor, suggesting an exhaustion of T-cell activation. French et al (2012) recently described high levels of IFNC/CD8CT cells in 12 metastatic lymph node tissues excised during the initial surgery, at patient presentation. The authors found that proliferating lymphocytes were evident in tumor-involved lymph node metastases that, in opposition to our findings, were enriched with PD-1C lymphocytes (French et al 2012).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Lymph node metastatic tissues had lower levels of B7H1 than the primary tumor, suggesting an exhaustion of T-cell activation. French et al (2012) recently described high levels of IFNC/CD8CT cells in 12 metastatic lymph node tissues excised during the initial surgery, at patient presentation. The authors found that proliferating lymphocytes were evident in tumor-involved lymph node metastases that, in opposition to our findings, were enriched with PD-1C lymphocytes (French et al 2012).…”
Section: Discussionmentioning
confidence: 98%
“…French et al (2012) recently described high levels of IFNC/CD8CT cells in 12 metastatic lymph node tissues excised during the initial surgery, at patient presentation. The authors found that proliferating lymphocytes were evident in tumor-involved lymph node metastases that, in opposition to our findings, were enriched with PD-1C lymphocytes (French et al 2012). They hypothesized that the presence of metastases does not arrest and may, on the contrary, promote an IFNC response, suggesting the generation of an antitumor response, which may impair tumor evasion.…”
Section: Discussionmentioning
confidence: 98%
“…107 Moreover, increased PD-1 C T cells in metastatic lymph nodes correlated with a more aggressive TC. 108 In a small PTC patient dataset, Foxp3 C Tregs and VEGF, evaluated by immunohistochemistry, were found in PTC samples and Treg infiltration correlated with disease stage and lymph node metastasis. 109 A higher Treg density was also observed in PTC samples compared with nodular goiter, and positively correlated to the stage of the disease.…”
Section: Natural Killer T Cells (Nkt) Gd T Cells and Innate Lymphoidmentioning
confidence: 95%
“…Divergent reports, however, have to be mentioned. In fact, the presence in PTC and metastatic nodes of T cells, macrophages, pDCs, and T reg cells was associated to increased tumor progression, invasion, node metastasis, and an overall decreased cancer-related survival [37].…”
Section: Cellular and Humoral Immune Responsementioning
confidence: 99%
“…IL-4 reduces the proliferation and impairs the function of cytotoxic CD8+ T cells. PTCderived DCs favor the differentiation of CD4+ T cells into T reg cells [44] that are increased in more aggressive PTC and node metastasis [37]. T reg cells are able to suppress NK cell functions.…”
Section: Cellular and Humoral Immune Responsementioning
confidence: 99%